Low-temperature activable, carbon dioxide based, highly adhesive and degradable oligo-urethane and its potential application as an auto-detachable dressing. (23rd May 2022) - Zhao, Chunjun; Zhang, Ruoyu; Han, Shuai; Yan, Xiaowen; Zhao, Keyu; Zhu, Xiaoxia; Han, Lijing
Abstract : Oligo-urethane based hot melt adhesives with UPy as the chain extender are developed with reduced activation temperature and improved adhesive strength. Especially, a oligo-urethane shows the possibility of being an excellent skin dressing. Abstract : Hot melt adhesives (HMAs) are being widely used in many areas. However, their high activation temperature complicates the operation and restricts their application, especially in medical treatment. In this work, we designed a low-temperature activable oligo-urethane-3 (OU-3) adhesive with a carbon dioxide (CO2 ) based ester as the soft segment and UPy as the chain extender and terminator. Compared to the known HMAs, its activation temperature could be as low as 60 °C. With a glued area of only 3.75 cm 2, its lap shear strength on a stainless steel matrix could be as high as 7.23 MPa. Furthermore, the use of OU-3 as a skin dressing was also evaluated. After being heated using a hair dryer for ∼10 s, the OU-3 film could be attached to a human elbow instantly and firmly. The skin dressing on the elbow area could be deformed with daily movement, and stably attached to the skin for at least 72 h. Its adhesion strength to pig skin could reach 30.7 kPa, proving its good stability on pig skin. The cytotoxicity, CCK-8, FGF2 level, water absorption and drug release experiments were also carried out to prove that the OU-3 dressing could absorb water while sustainably releasing the carried drugs in a safe way. After immersing in water for 15 min, the dressing automatically detached, which demonstrated good anti-water capability. Moreover, this implied that when its surface was fully wetted, OU-3 could auto-detach from the human skin, which could avoid secondary damage in medical treatment. Therefore, a prototype of an excellent skin dressing was demonstrated. Finally, the degradation of OU-3 in an enzymatic solution was also confirmed.